Effect of parthenolide on growth and apoptosis regulatory genes of human cancer cell lines. (January 2015) - Al-Fatlawi, Anees A.; Al-Fatlawi, Atheer A.; Irshad, Md.; Rahisuddin,; Ahmad, Ayaz
Abstract Context: Parthenolide (a sesquiterpene lactone), a bioactive compound of Tanacetum parthenium (L.) Schultz Bip. (Asteraceae) herb, has been reported for antioxidant and anticancer activities. Objective: The present study evaluated the effect of parthenolide on growth and apoptosis-regulatory genes of human cervical cancer (SiHa) and breast cancer (MCF-7) cell lines. Materials and methods: The cytotoxic activity of parthenolide (3.5–21 µM) was examined by MTT and LDH assays at 24 and 48 h time intervals. Apoptotic activity was evaluated by expression analysis of multiple apoptosis-regulatory genes (i.e., p53, Bcl-2, Bax, caspase-3, -6, and -9) by reverse transcriptase-PCR and DNA fragmentation assay. Results: Parthenolide inhibited the growth of SiHa and MCF-7 cell lines in a concentration-dependent manner at 24 and 48 h time intervals (p < 0.001). The IC50 value of parthenolide against SiHa and MCF-7 cells were 8.42 ± 0.76 and 9.54 ± 0.82 μM, respectively. Parthenolide-treated cells showed up-regulation of p53, Bax, caspase-3, -6, and -3 genes and down-regulation of Bcl-2 gene (p ≤ 0.008). At IC50, the p53 gene was up-regulated by 9.67- and 3.15-fold in SiHa and MCF-7 cells, respectively. The Bax to Bcl-2 ratio was 3.4 and 2.3 for SiHa and MCF-7 cells, respectively. Also, the fragmented genomic DNA in parthenolide-treated cells showed the signs of apoptosis. Conclusion: Our study endorsed the biological activity of parthenolide and demonstrated the parthenolide-induced growth inhibition and apoptosis in SiHa and MCF-7 cells by modulating the expression of apoptosis-regulatory genes.